Poligami: pengalaman dari perspektif isteri pertama - Nasrudin Subhi; Nurul Hidayah Mohd Nasir; Muhammad Ajib Abd Razak (Penerbit Universiti Kebangsaan Malaysia, 2020)
Polygamy is one of the family systems being practiced in Malaysia. The total number of men who practiced poligamy is increasing every year. In general, society has always viewed the experience of polygamy from a negative perspective particularly through the experience of the first wive. Thus the objective of this study is to explore the experiences from the perspective of the first wive towards full acceptance. The exploration focuses on elements of feeling, cognitive and behaviour. This research used the case study approach. Data was collected using semi-structured interview. Respondents consisted of three first wives aged 35, 43 and 57. Results showed that time are of an essence towards achieving full acceptance in polygamy. In terms of feelings two themes emerged which are jelousy and do not care. As for cognitive, three themes emerged in terms of their thinking position included positive, negative and contemplation. While their behaviours showed signs of aggression, passive and changing towards becoming a better person. The research finds that the first wives did experience significant impact particularly on their feelings, cognitive and behaviours which could affect their mental health status if not taken cared for properly. Therefore, or those intending to practice polygamy support from the husband and openness in the marriage are seen as important factors that needs to be taken into practice. The findings from this study are also hoped to assist counsellors and therapists to better understand polygamy thus becoming more competent in helping those in need.